Impact of COVID‐19 restrictions on pathology service utilisation. Issue 1 (20th January 2022) - Gillam, Marianne H.; Roughead, Elizabeth; Tavella, Rosanna; Dodd, Tom; Beltrame, John; Ryan, Richard; O'Loughlin, Peter
Abstract: Background: Isolation and social distancing restrictions due to COVID‐19 have the potential to impact access to healthcare services. Aims: To assess the use of pathology services during the COVID‐19 pandemic initial restrictions. Methods: Repeated cross‐sectional study of pathology tests utilisation during a baseline time period early in 2020 compared with pre‐lockdown and lockdown due to COVID‐19 in South Australia. The outcome measure was changed in a number of pathology tests compared to baseline period, particularly change in the number of troponin tests to determine potential impacts of lockdown on urgent care presentations. Results: In the community setting, the ratio of a number of pathology tests pre‐lockdown and post‐lockdown versus baseline period decreased from 1.02 to 0.53 respectively. The exception was microbiology molecular tests, where the number of tests was more than three times higher in the lockdown period. The number of troponin tests in emergency departments decreased in the lockdown period compared to the baseline time period; however, there was no evidence of an association between tests result (positive vs negative) and time period (odds ratio (OR) 1.09; 95% confidence interval (CI) 0.97–1.22). There was an inverse relationship between age and time period (OR 0.995; 95% CI 0.993–0.997), indicating that fewer troponin tests were conducted in older people during the lockdown compared with the baseline period. Conclusion: COVID‐19 restrictions had a significant impact on the use of pathology testing in both urgent and non‐urgent care settings. Further studies are needed to investigate the effect on health outcomes as a result of the COVID‐19 restrictions.